Classical guidance services think pair share method in increasing student self-confidence - Anggilina Prasetyasari; Dewi, Widya Novi Angga; Haksasi, Banun Sri; Kibtyah, Maryatul; Hidayat, Rahmawati (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2025)
Purpose – The purpose of this research is to find out how applying classical guidance services with the Think Pair Share method increases the confidence of students in class X TKP 1 at SMK Negeri 7 Semarang. Method – This research used a quantitative approach and Guidance Action Research (PTBK) method. The research subjects were 36 class X TKP 1 students, and the research location was held at SMK Negeri 7 Semarang. The data analysis used a Paired T-Test. Result – The results showed that the think-pair share method in classical guidance services effectively increased the self-confidence of students in class X TKP 1 at SMK Negeri 7 Semarang. This improvement can be seen from various indicators, such as confidence in self-ability, courage to express opinions, and ability to socialise. Implication – The result of this research is expected to provide a new variation for counselling teachers in conducting classical guidance learning with the think-pair share method, where this method can increase self-confidence in students. Originality/Value – This research is a research that discusses the implementation of classical guidance services using the think-pair share method to increase self-confidence in students. *** Tujuan – Tujuan penelitian ini adalah untuk mengetahui bagaimana penerapan layanan bimbingan klasik dengan metode Think Pair Share dapat meningkatkan kepercayaan diri siswa kelas X TKP 1 di SMK Negeri 7 Semarang. Metode – Penelitian ini menggunakan pendekatan kuantitatif dan metode Penelitian Tindakan Bimbingan (PTBK). Subjek penelitian adalah 36 siswa kelas X TKP 1, dan lokasi penelitian dilakukan di SMK Negeri 7 Semarang. Analisis data menggunakan uji t berpasangan. Hasil – Hasil penelitian menunjukkan bahwa metode think-pair share dalam layanan bimbingan klasik secara efektif meningkatkan kepercayaan diri siswa kelas X TKP 1 di SMK Negeri 7 Semarang. Peningkatan ini dapat dilihat dari berbagai indikator, seperti kepercayaan diri dalam kemampuan diri, keberanian untuk mengemukakan pendapat, dan kemampuan bersosialisasi. Implikasi – Hasil penelitian ini diharapkan dapat memberikan variasi baru bagi guru bimbingan konseling dalam melaksanakan pembelajaran bimbingan klasik dengan metode think-pair share, di mana metode ini dapat meningkatkan kepercayaan diri siswa. Orisinalitas/Nilai – Penelitian ini merupakan penelitian yang membahas implementasi layanan bimbingan klasik menggunakan metode think-pair share untuk meningkatkan kepercayaan diri siswa.